Utilization of long-lasting insecticide-treated net and its associated factors among pregnant women in Dawo district, Southwest Shoa Zone, Oromia, Ethiopia, 2023 - Negasa, Kumsa; Huluka, Tufa Kolola; Yebassa, Mecha Aboma; Waqkene, Tolossa (Frontiers in Public Health, 2024)
The use of long lasting insecticide-treated net (LLIN) is one of the most effective malaria prevention strategies, particularly among pregnant women. It has mosquito-killing, repellent, and physical barrier properties. Pregnant women, children under 5 years of age and patients with HIV/AIDS, as well as non-immune migrants, mobile populations and travelers are the most vulnerable groups for malaria. Even when pregnant women are given priority, not all nets owned by households are used by pregnant women. Therefore, risk of the occurrence of malaria in pregnancy is also high.Objective: This study aimed to assess the utilization of long-lasting insecticide-treated net and its associated factors among pregnant women in Dawo district,